State and organization of polyoma virus DNA sequences in transformed rat cell lines. - Birg, F (1979)
Polyoma virus-transformed rat cell lines were isolated as colonies growing in agar after infection of F2408 cells with low multiplicities of wild-type virus. Viral DNA present in the transformed cells was analyzed by fractionating the cellular DNA on agarose gels before and after digestion with various restriction endonucleases, followed by detection of the DNA fragments containing viral sequences using the procedure described by Southern (E. Southern, J. Mol. Biol., 98:503--515, 1975). Five lines, independently derived, were studied in detail. All five lines, when examined after a minimum number of passages in culture, contained both free and apparently integrated viral DNA. The free polyoma DNA in three of the lines was indistinguishable, by restriction enzyme analysis, from wild-type viral DNA, whereas the two other lines also contained smaller free DNA molecules which lacked parts of the wild-type genome. The integrated DNA in the five lines studies existed as head-to-tail tandem repeats of unit-length polyoma DNA covalently attached to nonviral DNA. The same five polyoma-transformed rat lines were examined after further passage in culture. Free viral DNA was then either undetectable or greatly reduced in amounts, whereas the high-molecular-weight, integrated units persisted after passage of the cells. The subclones, derived from one of the five lines selected for detailed analysis, showed some variations in the quantity and size of the free viral DNA as well as minor alterations in the pattern of the apparently integrated sequences.